Migraine in a pediatric population: a clinical study in children younger than 7 years of age. (14th January 2015) - Raieli, Vincenzo; Pitino, Renata; Giordano, Giuliana; Spitalieri, Chiara; Consolo, Flavia; Puma, Domenico; Santangelo, Giuseppe; Vanadia, Francesca; D'Amelio, Marco
<x xml:space="preserve">Abstract</x> Aim Migraines in children younger than 7 years of age have received limited attention in the published literature. The aim of this study is to describe the characteristics of migraine phenotypes in children younger than 7 years, and to compare them with migraines in children older than 7 years of age. Method We reviewed all standard clinical files, collected over 4 years, related to children with a diagnosis of primary headache. We included all children younger than 7 years diagnosed with migraine in our study. Results A total of 374 children (188 males, 186 females) were affected by migraine with/without aura: 40 of these patients (10.7%; 20 males, 20 females; mean age 5y 7mo, SD 1y 2mo) where younger than 7 years old. The frequencies of the main migraine features in the younger age group were similar to those of children older than 7 years, with the exception of a shorter duration of migraine and reduced frequency of attacks. Interpretation In children younger than 7 years of age, the clinical phenotype of migraine is similar to that seen in older children. We propose that there is a general genetic migraine susceptibility that, in the presence of activating environmental factors, may induce typical attacks of migraine in individuals already predisposed to migraine attacks. Therefore, different modules induce different clinical features within the different age groups, but there is no difference in the frequencies of clinical phenotypes between the two age groups.